The effect of antibiotics (Aureomycin-B12 supplement) on weaning pigs in the dry lot - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
The use of antibiotics in swine nutrition has received much attention the last few years. Research has shown that different vitamin B12 antibiotic supplements stimulate gains and improve feed efficiency in growing and fattening swine. One problem arising from its use is the relative efficiency of the B12-antibiotic supplement in plant protein supplement diets and in mixed plant and animal protein supplement diets.
Keywords: Swine; Antibiotics; Aureomycin-B12; Dry lot; Protein